2019
DOI: 10.3390/ani9020039
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Energy Levels Affect Growth Performance through Growth Hormone and Insulin-Like Growth Factor 1 in Yak (Bos grunniens)

Abstract: The objective of this study was to investigate the effects of different dietary energy levels on serum concentrations of growth hormone (GH) and insulin-like growth factor 1 (IGF-1), as well as gene expression of their associated binding proteins and receptors in yak. Fifteen adult male yaks with BW of 276.1 ± 3.5 kg were allotted in three dietary groups and were fed with low (LE), medium (ME), and high energy (HE) level diet having different NEg of 5.5 MJ/kg, 6.2 MJ/kg, 6.9 MJ/kg, respectively. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The growth performance of yaks has been previously reported ( Yang et al, 2019 ). The final body weights of YM and YH group animals were significantly higher than those in the YL group ( P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The growth performance of yaks has been previously reported ( Yang et al, 2019 ). The final body weights of YM and YH group animals were significantly higher than those in the YL group ( P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
“…Acetate and butyrate are used for fat synthesis and energy supply, while propionate is the main source of glucose for ruminants ( Den Besten et al, 2013 ). We recorded high feed efficiency in yaks from YM and YH groups, which could be explained by a significant increase in concentrations of VFA with the resulting increase of metabolizable energy content of the feed ( Yang et al, 2019 ). High concentrations of acetate, propionate, and valerate in rumen of high milk-producing Holstein dairy cows were reported ( Xue et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Renaville et al (2002) reported that GH synthesized in the pituitary gland and acts directly on liver and adipose tissue to regulate gluconeogenesis, proteosynthesis, lipogenesis, lipolysis, and insulin secretion by binding to growth hormone receptor (GHR). Meanwhile, the existence of the axis between GH and IGF-1 has played a vital role in the regulation of metabolism and GHR combines with GH to stimulate a series of metabolic activities by producing IGF-1 in the target tissues, especially in liver (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…After clotting at room temperature, sera were separated by centrifugation at 1,800 g for 20 min and transferred to plastic tubes. Sera were stored at -20 ºC for subsequent GH concentration analysis by using a commercial ELISA kit (Beijing Sino-UK Institute of Biological Technology, Beijing, China) according to Yang et al (2019). Serum glucose concentration was measured by the glucose/oxidase method using a commercial kit (Biolabo, Glucose GOD-PAP, Cat.…”
Section: Blood Samples and Serum Analysismentioning
confidence: 99%